Caracterização morfométrica da raça Mangalarga Marchador - Juliano Martins Santiago (2013)
Morphometric assessment of horses is an important instrument selection, because it is related to the functionality of this species. In the first chapter we evaluated the evolution of morphometric measurements of Mangalarga Marchador (MM). We used linear measures stored in the database of the Genealogical Registry Service, in a completely randomized design, with treatments consisting of the years between 1970 and 2010. The selection of race MM gave the animals shorter head, greater stature, shorter torso length and larger diameter of the bony rays. In the second chapter we compared measures of the current herd MM with exemplary champions, and were determined morphometric measures of the true type of race. The design was completely random, and the treatments for the herd MM registered between 2000 and 2010, and the animals champions measured for three national expositions. The differences between the measurements of mares champions, relative the herd of females, are larger which among horses champions and herd male. Although champions horses MM present greatest linear measurements, they are proportionally similar to the population of the breed. In the third chapter we compared morphometric measures of MM horses of categories batida and picada marcha. We compared morphometric measurements of horses in both categories, in a completely randomized design. In MM horses of categories batida and picada marcha most of the measures have similar values, however, there are differences between some angles of members.